Review of Economic Studies European Meetings (Review of Economic Studies, 2000)
Journal Article Review of Economic Studies European Meetings Get access The Review of Economic Studies, Volume 67, Issue 4, October 2000, Page 811, https://doi.org/10.1111/1467-937X.00155 Published: 01 October 2000